First Language Acquisition: Towards Strategy-Oriented Perspective - Shirazi, Masoumeh Ahmadi; Nemati, Majid (Mediterranean Journal of Social Sciences, 2012)
A lot has been allocated to how a child learns to talk, but what has been neglected is the reason why he starts to. Satisfying biological needs, at most, would have been the first objective of the child. However, what he intends is communication for which the primitive signs and gestures are transformed into codes whether it be sounds uttered or figures engraved on the papers. Strategy leads the child to find his way into the community he belongs to, and language just like other abilities develops as he grows up biologically. His experience with otherese assists him to find the path, explore, experiment, practice and get involved with meaning-geared communication for which he goes all out to use linguistic aspects. In almost all developmental processes, when the child is not able to express oneself clearly, compensation strategies are resorted to in order for his/her intentions to become realized. However, these long-lasting strategies are not erased with the passage of time since they are taken to be devices of perfect versatility which appears to last for a lifelong period.